ON TRENDS TO IMPROVE THE LEGAL REGULATION OF THE EMPLOYEES’ INCENTIVES - Вишновецький, Вадим Михайлович; Гуцал, Ілона Юріївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: to determine the trends to improve the legal regulation of the employee’s incentives. Research methods: analysis, synthesis, generalization, comparison, etc. Results: to deem it necessary to make a separate chapter in the Labour Code «Incentives for Work» which shall increase the role of stimulating norms in regulation of labour relations. Discussion: the modern realities require wider use of motivation and incentives to keep the most skilled employees. Nowadays the problem of improving the legal regulation of incentives in the labour legislation of Ukraine becomes especially relevant. The Labour Code of Ukraine stipulates a requirement to the employees to perform their duties conscientiously. Analysing the norms of the Labour Code of Ukraine we make a conclusion that the incentives are benefits of material or moral nature, benefits or advantages with which the employer honour the employee’s labour merits. At the same time, there is no legal consolidation of the concept of labour merit as a ground to apply the incentives. Since the Article 139 of the Labour Code of Ukraine determines the obligation of the employees to work honestly and conscientiously, timely and accurately perform the orders of the owner or its authorized body, scientists do not consent on whether any conscientious performance of the task (within or exceeding indicators) is a legal ground to apply the incentives, whether there should certainly be achievements in work (increased productivity, innovation, etc.), success in work. As the merit is considered as a ground to apply the incentives, the labour merit concept needs to be legally specified. It is concluded that the employee’s stimulation in the form of incentives are effective, if they are transparent and timely. To ensure transparency, it is necessary to determine clearly the types of incentives, the grounds and procedure for their application, as well as the performance indicators, according to which the employee is honoured with any type of the incentive in the local regulations of the company. It is necessary that the legal grounds and conditions of the incentives should be formalized so that the employer could not guide solely by its own desire. After all, the Article 144 of the Labour Code of Ukraine states that stimulation of the employee is the employer’s right, but not its obligation. That is, it may, at its own discretion, determine the appropriateness to apply (or not apply) the incentives to a particular employee. And for timeliness, it is important to stimulate the employees not only on the days of professional holidays «for good», but to respect a man of work every day. We share the position of those scholars who propose to make a separate chapter in the Labour Code of Ukraine «Incentives for Work», which will increase the role of incentives in the regulation of labour relations.